Cardiovascular risk factors in adults with coarctation of the aorta. (17th May 2019) - Fedchenko, Maria; Mandalenakis, Zacharias; Dellborg, Helena; Hultsberg‐Olsson, Görel; Björk, Anna; Eriksson, Peter; Dellborg, Mikael
Abstract: Background: The aging patient with adult congenital heart disease (ACHD) faces the risk of developing atherosclerotic disease. Patients with coarctation of the aorta (CoA) are especially vulnerable because of an inherent high risk of developing hypertension. However, data on the prevalence of other cardiovascular risk factors are scarce. Therefore, this study aimed to describe the prevalence of traditional cardiovascular risk factors (diabetes, hypertension, hyperlipidemia, smoking, obesity, and sedentary lifestyle) in adult patients with CoA. Methods: Patients with CoA who were registered at the ACHD clinic in Gothenburg were asked to participate in a comprehensive cardiovascular risk assessment. This assessment included a glucose tolerance test, cholesterol profile, ambulatory blood pressure measurements, and a lifestyle questionnaire. Results: A total of 72 patients participated. The median age was 43.5 years and 58.3% were men. Sixty‐six (91.7%) patients had ≥one cardiovascular risk factor and 40.3% had ≥three risk factors. Three (4.2%) patients were newly diagnosed with diabetes or impaired glucose tolerance. More than half of the patients had hyperlipidemia ( n  = 42, 58.3%) and 35 patients (48.6%) were overweight or obese. Only three (4.2%) patients smoked regularly. Of the 60 patients who underwent 24‐hour ambulatory blood pressure measurement, 33 (55.0%) were hypertensive. Of the 30 patients with known hypertension only 9 (30.0%) had well‐controlled blood pressure on ambulatory blood pressure measurement. Conclusions: Cardiovascular risk factors among patients with CoA are prevalent. This may indicate a need for more aggressive screening strategies of traditional risk factors to minimize the risk of these patients also developing atherosclerotic disease.